TURNING IDEAS INTO TEXT: PROJECT-BASED LEARNING IN WRITING INSTRUCTION - Indah Khoirun Nisa; Farah Ika Damayanti; Muhammad Yunus (SOSIOEDUKASI, 2026)
While new teaching model has the potential to develop teaching writing practices, the shift from traditional teacher-centered methods to Project-Based Learning (PBL) remains underexplored in secondary school contexts. This current study addresses this gap by evaluating the effectiveness of PBL in improving students’ writing competencies. The data were obtained through classroom action research with pre-test and post-test. The findings indicate a significant improvement in students’ writing skills. The students' average scores improved from 65.8 in the pre-test to 72 in the first cycle and 80.1 in the second cycle. These results demonstrate significant enhancement in students' writing abilities following the implementation of PBL. Overall, PBL is considered an effective teaching practice for improving writing skills through problem-solving and collaborative learning. It also fosters critical thinking and creativity among students. Furthermore, this study provides practical insights for educators and curriculum developers on using PBL as a method to improve students' writing proficiency.